Answer: x=2
3x+2y=12 and y=2x-1 so you already know what y equals. Substitute y into the first problem.
Step-by-step explanation: 3x+2y=12 will turn into
3x + 2(2x-1) = 12 now multiply the 2 on the outside to the inside numbers
3x + 4x - 2 = 12 then combine the x's
7x - 2 = 12 after you are going to add 2 to both sides
+2 = +2 (the negative 2 and positive 2 cancel each other out)
7x = 14 then divide 7 to both sides which gets you 2
If you place 2 back into y=2x-1 you'll get y=2(2)-1 which is y=4-1 so y=3
so 3x+2y=12 will become 3(2) + 2(3) = 12